CONTROLLED BURNS EFFECT ON SOIL CHEMICAL PROPERTIES - White, Benjamin Leonardo Alves; Lima, Layanne Oliveira de Jesus (Floresta, 2023)
Controlled burns have been used to manage pastures, forests and agricultural fields for centuries. Defended by some and criticized by others, until today, there is still no consensus in the scientific community about the effects caused by fire on soil. This study had the objective to analyze the effect of controlled burns on soil pH, H+Al, Al3+, Na+, K+, P, O.M., Ca2+, Mg2+, and N. For this propose, two different pasture plots were burned and had the fire intensity quantified. The burned soil, and from an adjacent control plot, were collected at three different moments: immediately, one and six months after the burns. The burns presented low intensity ranging from 23,7 to 30,91 kJ m-1 s-1. Immediately after the burns the values of pH, Na+, Ca2+, K+ and P increased in the burned plots and were significantly different from the control plot. However, six months after the burns, only the amounts of K+, P and Ca2+ remained significantly larger than the controlled. Despite the values of the N and H+Al in burned and control areas were similar immediately and one month after the burns, after six months the amount of N was significantly larger in one of the burned plot, while the H+Al was significantly bigger in the control plot. The amounts of Mg2+, O.M. and Al3+did not change during the study period. The found results suggest that low-intensity controlled burns can reduce soil acidity and be effective in increasing some essential nutrients for plant development in short term.